Solvents on Phytochemical and Organoleptic Properties of Basella alba: Potential for Development of Diabetes Drugs - Ernawati Ernawati; Aris Prastyoningsih; Agnes Prawistya; Dono Indarto; Najwa Nur Hidayati; Firda Aprilia Rahmayanti (GLOBAL HEALTH SCIENCE GROUP, 2026)
The content of basella alba shows that phenolic compounds can also act as inhibitors of the α-amylase and α-glucosidase enzymes, thus providing an anti-hyperglycemic effect. However, the influence of different solvents on its phytochemical composition, organoleptic characteristics, and bioactive compound content remains underexplored. Leaves of B. alba collected from Central Java, Indonesia, were shade-dried, powdered, and extracted separately using ethanol (EEBA), methanol (MEBA), and water (AEBA) via maceration for 3 × 24 hours. Extracts were filtered, concentrated using a rotary evaporator, and evaluated for organoleptic traits, phytochemical profiles, total flavonoid content (TFC), total phenolic content (TPC), antioxidant activity (DPPH assay, IC₅₀), and pH. The aqueous extract (AEBA) produced the highest yield (7.95%) but contained fewer bioactive metabolites compared to organic solvents. Phytochemical screening revealed that MEBA contained alkaloids, flavonoids, triterpenoids, saponins, steroids, tannins, and phenolics; EEBA showed similar profiles except for alkaloids; while AEBA lacked alkaloids and flavonoids. Quantitative analysis indicated that MEBA had the highest flavonoid content (35.20 mg QE/g), whereas EEBA had the highest phenolic content (25.28 mg GAE/g). Antioxidant activity analysis showed MEBA exhibited the strongest effect (IC₅₀ = 284.43 µg/mL), followed by EEBA (436.84 µg/mL) and AEBA (1129.37 µg/mL). The pH values of all extracts were comparable (6.54–6.62). While water produced the highest yield, methanol proved most effective in extracting phenolics, flavonoids, and alkaloids, thereby yielding superior antioxidant potential. Ethanol also extracted substantial flavonoid content, though without alkaloids. These results highlight methanol as the most effective solvent for isolating antioxidant-related compounds from B. alba leaves.